2009
DOI: 10.1016/j.niox.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The resistance of electron-transport chain Fe–S clusters to oxidative damage during the reaction of peroxynitrite with mitochondrial complex II and rat-heart pericardium

Abstract: The effects of peroxynitrite and nitric oxide on the iron-sulfur clusters in complex II (succinate dehydrogenase) isolated from bovine heart have been studied primarily by EPR spectroscopy and no measurable damage to the constitutive 2Fe-2S, 3Fe-4S, or 4Fe-4S clusters was observed. The enzyme can be repeatedly oxidized with a slight excess of peroxynitrite and then quantitatively rereduced with succinate. When added in large excess, peroxynitrite reacted with at least one tyrosine in each subunit of complex II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
(53 reference statements)
2
25
0
Order By: Relevance
“…The intensity of the signal at g = 2.02 (actually the maximum of the S-shaped line is at g = 2.02) does not vary much between 30 K and 20 K (Fig. 1B), which is consistent with saturation of the line for [3Fe-4S] 1+ [52]. This signal is consistent with mitochondrial aconitase because it does not have a shoulder to the left of the g = 2.02 signal that would be expected for cytosolic aconitase [70].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The intensity of the signal at g = 2.02 (actually the maximum of the S-shaped line is at g = 2.02) does not vary much between 30 K and 20 K (Fig. 1B), which is consistent with saturation of the line for [3Fe-4S] 1+ [52]. This signal is consistent with mitochondrial aconitase because it does not have a shoulder to the left of the g = 2.02 signal that would be expected for cytosolic aconitase [70].…”
Section: Resultssupporting
confidence: 75%
“…Aconitase is susceptible to oxidative inactivation, particularly by O 2 •− , which results in the release of a labile iron (Fe) from its catalytic 4Fe-4S center resulting in an inactive [3Fe-4S] 1+ species that can be detected by EPR [56-59]. While the activities of complexes I, II, and III can be inhibited by a number of oxidants (see above), their Fe-S centers are generally resistant to oxidants [52, 60]. Complex I activity, in particular, is quite sensitive to the thiol redox status of mitochondria [61, 62], which could explain its inhibition under some conditions of oxidant stress.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the level of inhibition in SDH is substantially less than that of aconitase, which is by far the most pro-oxidant susceptible CAC enzyme (250). Indeed, Pearce et al (243) showed that SDH is relatively resistant to ONOO À -mediated oxidative damage, suggesting that SDH has a more robust iron-sulfur center construction than aconitase. Despite this relative stability in the presence of oxidative stressors, inactivation of SDH secondary to oxidative damage to its iron-sulfur centers may have significant epigenetic ramifications due to downstream effects of succinate-based inhibition of epigenetic enzymes.…”
Section: Cyr and Domannmentioning
confidence: 99%
“…The spin-Hamiltonian parameters, midpoint potentials and relaxation behavior of these centers have been reasonably well characterized (6987), along with some other tissue-specific signals from transferrin, ceruloplasmin, and catalase (8890). Specific applications of EPR to mitochondria have included detection of an irreversible deficiency in Complex I FeS clusters in iron-deficient rats (91), heme-nitrosyl in substantia nigra of Parkinson’s diseased brain (92), chromium-dependent inhibition of Complexes I & II and aconitase (93), cardio- and neuro-protection against doxorubicin (80), prophylaxis against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine in a Parkinson’s mouse model (82), the differential sensitivity of aconitase and FeS clusters from Complexes I & III to oxidative and nitrosative stress in heart (94), and the sensitivity of Complex III FeS clusters in aging heart to ischemia (95). However, despite these successes in mechanistic studies, the authors are unaware of any direct application of EPR for functional pathophysiologic studies in humans or whole animal models with primary mitochondrial disease; the closest analog is a study in which a comparison of EPR signals from muscle biopsies of sepsis patients indicated significant depletion of Complex I FeS signals in those who died compared to survivors (86, 96).…”
Section: Introductionmentioning
confidence: 99%